2012
DOI: 10.1371/journal.pntd.0001631
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation-Independent Methods Reveal Differences among Bacterial Gut Microbiota in Triatomine Vectors of Chagas Disease

Abstract: BackgroundChagas disease is a trypanosomiasis whose agent is the protozoan parasite Trypanosoma cruzi, which is transmitted to humans by hematophagous bugs known as triatomines. Even though insecticide treatments allow effective control of these bugs in most Latin American countries where Chagas disease is endemic, the disease still affects a large proportion of the population of South America. The features of the disease in humans have been extensively studied, and the genome of the parasite has been sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
97
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(116 citation statements)
references
References 61 publications
(94 reference statements)
14
97
4
1
Order By: Relevance
“…Some differences in the taxonomic composition of triatomine gut bacterial communities were found in our study, in comparison with previous results obtained with non-culture- [19, 20] and culture-based methods (reviewed in great extension by Vallejo et al [32]). A significant absence in our samples is Serratia , a genus of bacteria that have trypanolytic activity on specific T. cruzi strains [12].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Some differences in the taxonomic composition of triatomine gut bacterial communities were found in our study, in comparison with previous results obtained with non-culture- [19, 20] and culture-based methods (reviewed in great extension by Vallejo et al [32]). A significant absence in our samples is Serratia , a genus of bacteria that have trypanolytic activity on specific T. cruzi strains [12].…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, the ability of some T. cruzi strains to develop in certain vector species depends on the intrinsic qualities of either the parasite or the insect vector, as well as the resident host gut microbiota [18]. Previous studies using non-culturing based methods [19, 20] identified some triatomine gut microbiota characteristics: first, its diversity within each host is low with only one or few genera being dominant; secondly, some bacterial genera appear to be specific to certain triatomine hosts, i.e. Rhodococcus to Rhodnius and Arsenophonus to Triatoma ; finally, lab-reared insects lose part of the original microbiota diversity but conserve most of the bacterial groups found in their wild counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…These results are also in accordance with a study by da Mota et al in 2012 that reported the characterization of the bacterial symbionts found in four triatomine genera, including two species of the Triatoma genus that inhabit South America (Triatoma infestans and T. vitticeps) (da Mota et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported a low diversity of bacteria associated with the microbiota of triatomine insects in comparison to other insect groups (Vallejo et al, 2009;da Mota et al, 2012;Gumiel et al, 2015). Our results agree with this observation since we found only 14 different 16S rRNA sequences among all field collecting sites, laboratory specimens, and life stages of the insects.…”
Section: Discussionsupporting
confidence: 91%
“…eDNA methods are more recently being applied to other hosts for example mammals [90], plants [91], and invertebrates. Examples of the latter include the use of 16S rDNA denaturing gradient gel electrophoresis (DGGE) and clone sequencing to suggest that vector gut microbiota may influence transmission and virulence of Trypanosoma cruzi [92], similar methods used for understanding gut microbiota assembly in the western corn rootworm (Coleoptera) and their potential as pathogen vectors [93], variation in bumble bee gut bacteriome between related species and how this varies with pathogen infections [94], and the suggestion via metatranscriptome sequencing that shifts in honey bee gut bacteria/community may be a marker of CCD [86]. Pathogens in the microbiotic environment in which organisms live are also important for health and as selective agents: metabarcoding of bacterial communities local to European minnow populations has shown that host-parasite interactions drive local adaptation of the major histocompatibility complex (MHC) class IIB loci, in relation to local pathogen diversities [95].…”
Section: Potential For Development Of Edna Methods In Parasitologymentioning
confidence: 99%